Optics outreach activities with elementary school kids from public education in Mexico - Viera González, Perla Marlene; Sánchez Guerrero, Guillermo Ezequiel; Ruiz Mendoza, Juan Carlos; Cárdenas Ortiz, G.; Ceballos Herrera, Daniel E. (2023)
This work shows the results obtained from the “O4K” Project supported by International Society for Optics and Photonis (SPIE) and the Universidad Autonoma de Nuevo Leon (UANL) through its SPIE Student Chapter and the Dr. Juan Carlos Ruiz-Mendoza, outreach coordinator of the Facultad de Ciencias Fisico Matematicas of the UANL. Undergraduate and graduate students designed Optics representative activities using easy-access materials that allow the interaction of children with optics over the exploration, observation and experimentation, taking as premise that the best way to learn Science is the interaction with it. Several activities were realized through the 2011-2013 events with 1,600 kids with ages from 10 to 12; the results were analyzed using surveys. One of the principal conclusions is that in most of the cases the children changed their opinions about Sciences in a positive way